Innovations in Knowledge Management The Impact of Social Media, Semantic Web and Cloud Computing - Razmerita, Liana; Phillips-Wren, Gloria; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book discusses emerging trends in the field of managing knowledge work due to technological innovations. The book is organized in 3 sections. The first section, entitled "Managing Knowledge, Projects and Networks", discusses knowledge processes and their use, reuse or generation in the context of an organization. The second section, entitled "Managing Knowledge using Social Media", focuses on factors influencing adoption and usage, the role of social media in managing knowledge, and factors that influence employees' acceptance and participation. The third section brings into discussion new approaches and technologies for acquiring knowledge. The book will be useful to both academics engaged in research in knowledge management and practitioners who are considering or implementing strategies for managing one of their most important resources.
Managing Knowledge, Projects and Networks -- Managing Knowledge using Social Media: factors influencing adoption and usage -- New Approaches and Technologies for Knowledge Acquisition.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence